Development of a Debate Learning Model, Analysis, and Findings Based on Digital Life Skills for Elementary Schools - Apdoludin; Guswita, Reni; Andriani, Diyan; Putri, Dexza Isma (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to determine the validity, practicality, and effectiveness of the developed digital life skill-based DAT learning model. It used development research (R&D). The population of this research was 124 students of grade IV of SDN 106/II Sungai Binjai, Bathin III District, Bungo Regency, Jambi Province, Indonesia, and the sample was 36 students chosen using simple random sampling. Data collection techniques were model validation sheets, observations, questionnaires, and interviews. The validity of the instrument used in this research was content validity by consulting with experts. The reliability test in this research used a Likert scale. The research results indicate that (1) the debate, analysis, and findings model based on digital life skills improves students' thinking skills, trains students' skills, and can help students analyze learning in depth, 2) through the debate, analysis, and findings model based on digital life skills, the learning takes place more systematically, and significant in improving student understanding, and (3) learning with the debate, analysis, and findings model based on digital life skills can make learning more effective.